2013
DOI: 10.1371/journal.pgen.1003616
|View full text |Cite
|
Sign up to set email alerts
|

The Conserved ADAMTS-like Protein Lonely heart Mediates Matrix Formation and Cardiac Tissue Integrity

Abstract: Here we report on the identification and functional characterization of the ADAMTS-like homolog lonely heart (loh) in Drosophila melanogaster. Loh displays all hallmarks of ADAMTSL proteins including several thrombospondin type 1 repeats (TSR1), and acts in concert with the collagen Pericardin (Prc). Loss of either loh or prc causes progressive cardiac damage peaking in the abolishment of heart function. We show that both proteins are integral components of the cardiac ECM mediating cellular adhesion between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(90 citation statements)
references
References 50 publications
8
82
0
Order By: Relevance
“…4E). This phenotype is strikingly similar to other cardiac extracellular-matrix mutants, such as Lonely heart (loh) (Drechsler et al, 2013). To determine whether pericardial cells detached in the context of abnormal extracellular-matrix formation, we stained the flies for pericardin, a type IV collagen that is crucial for maintaining cardiac integrity in Drosophila.…”
Section: Misexpression Of Nedd4 Disrupts the Patterning Of Cardioblassupporting
confidence: 53%
“…4E). This phenotype is strikingly similar to other cardiac extracellular-matrix mutants, such as Lonely heart (loh) (Drechsler et al, 2013). To determine whether pericardial cells detached in the context of abnormal extracellular-matrix formation, we stained the flies for pericardin, a type IV collagen that is crucial for maintaining cardiac integrity in Drosophila.…”
Section: Misexpression Of Nedd4 Disrupts the Patterning Of Cardioblassupporting
confidence: 53%
“…Fibrosis can be visualized in whole-mount hearts using confocal microscopy with actin-phalloidin staining or immunohistochemistry for extracellular matrix proteins such as collagens (especially pericardin), perlecan and the ADAMTS (a disintegrin and metalloprotease with thrombospondin repeats) homolog Lonely heart (Chartier et al, 2002;Drechsler et al, 2013). Stimulation-induced heart failure can also be measured in whole flies using external electrical pacing (Wessells et al, 2004).…”
Section: The Heartmentioning
confidence: 99%
“…Nevertheless, flies with certain genetic defects in cardiac development and function suffer from reduced fitness and longevity (e.g. Drechsler et al, 2013;Ocorr et al, 2007). However, specific manipulations of the cardiac ECM may increase longevity (Sessions et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this restriction is the fact that during diastole we observed backflow of particles from the aorta into the posterior heart chamber, which we consider artificial and caused by the preparation procedure (see Movie 2C). Visualising haemolymph streaming in intact specimens showed that in larvae and prepupae haemolymph streaming is unidirectional (Choma et al, 2011;Drechsler et al, 2013). This indicates that unidirectional haemolymph flow inside the heart tube is affected by the dissection procedure, presumably due to an impaired connection of the heart tube to the alary muscles.…”
Section: Intracardiac Valve Cells -Mode Of Operationmentioning
confidence: 99%
See 1 more Smart Citation